Uncovering The Sociological Interpretation of Visual Impairment-Related Inequities and Their Social Determinants in India - M, Chandrashekher; Satpathy, Suchismita (National Journal of Community Medicine, 2023)
Introduction: Determinants of health are divided into four types, such as “Biological-Psychological-Environmental-Social Determinants”. The social determinants of health include gender disparities, economic status, ethnicity, race, geographic isolation, or having a specific health condition. Moreover, the social determinants are interdependent and interrelated with one another. There can also be a primary determinant that affects the other determinants. For example, educational level of the patients is associated with knowledge and awareness of eye care and its conditions. However, education might have a different effect than income in should be access of eye care when needed. Methodology: The study is mainly dependent on secondary data analysis. Results: The primary objective of the study is to illustrate the sociological aspects of visual impairment-related inequities and to identify the social determinants of visual impairments and disparities in India. Another aim of the paper is to present a deeper understanding of how inequities impact the incidence of visual impairment and blindness based on the social determinants of health. The present study adopts the ecological and Commission on Social Determinants of Health (CSDH) framework 2008. We reaffirm the fact that inequities negatively affect the visual impairment and blindness conditions. The national health policies should take into account the social determinants of visual impairment in their policies relating to comprehensive eye care. Social and economic factors are connected with health and welfare; those socio-economic inequalities contribute to health inequalities. For reducing the health inequalities around the world, we need effective policy implementation and proper fund pools. Furthermore, committed action on societal determinants of health, sufficient human resources are also necessary to control the health disabilities, include visual impairment.